Hubungan Self-Efficacy Kualitas Hidup Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialis Di RS Royal Prima Medan - Lase, Yuvriani; Karlina Susanti Lase, Wanda; Sihotang, Tulus; Salsabilla, Nazwa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Chronic kidney disease is kidney damage that lasts for three months or more, characterized by a gradual and permanent decline in kidney function. Chronic kidney disease patients undergoing hemodialysis experience a decreased quality of life. The purpose of this study was to determine the relationship between self-efficacy and quality of life in chronic kidney failure patients undergoing hemodialysis at Royal Prima Hospital Medan. The study was a cross-sectional study. The sampling technique used a total sampling of 45 participants. Data were collected using a questionnaire. Data were analyzed using the Chi-Square test. The results showed a relationship between self-efficacy and quality of life in chronic kidney failure patients undergoing hemodialysis. Hospital management is recommended to implement self-efficacy as an intervention for palliative care patients.